plaNext in transition: A decade of young academic publishing in planning (2015–2025) – Insights and futures - Asma Mehan (PlaNext)
This article reflects on the ten-year journey of plaNext – Next Generation Planning, an open-access, peer-reviewed journal initiated by the AESOP Young Academics Network (AESOP-YAN). First published in 2015, plaNext has served as a platform for early-career researchers to engage in planning debates, publish their work, and foster professional development. As the journal approaches its tenth anniversary, this reflection examines its history, legacy, and future directions, highlighting its role in promoting inclusive, critical, and innovative scholarship in the field of planning. Over the past decade, plaNext has evolved into a dynamic forum that publishes diverse contributions, fosters international dialogues, and challenges conventional planning paradigms. The journal’s commitment to promoting interdisciplinary dialogues is evident in its eclectic range of published works, encompassing empirical research, theoretical discussions, innovative methodologies, and critical case studies. This breadth reflects plaNext’s mission to serve as a conduit for creative and socially responsive planning research. As the journal evolved, it remained steadfast in its dedication to nurturing the professional development of young academics by providing opportunities for early-career researchers to engage in editorial processes, peer review, and scholarly debates. As plaNext transitions to a new editorial board, this article offers a comprehensive overview of its evolution and impact. Drawing on the journal’s trajectory and broader shifts in planning scholarship, the discussion highlights the critical role of platforms like plaNext in shaping the discipline’s future.